SAT0333 Hemostatic Mechanisms May Play A Role in The Development of Thrombosis in Male Patients with Behcet's Disease: A Thromboelastographic Analysis. (15th July 2016) - Kara Kivanc, B.; Gonullu, E.; Bal, C.; Akay, M.O.; Erturk, A.; Uskudar Cansu, D.; Kasifoglu, T.; Korkmaz, C.
Abstract : Background: In Behcet's disease (BD), vascular involvement is seen frequently in young male BD patients. However, its reason is not well known. Objectives: Our aim was to compare thrombotic tendency according to gender by using the modified Rotational Thromboelastography parameters and platelet-leucocyte complex levels. Methods: 126 BD patients (71 male, 55 female; mean age:41±9 yrs) who met ISSG criteria for Behcet's disease were included into study. This group was divided into 3 subgroups as non-thrombotic (n=73), acute thrombotic (n=25) and chronic thrombotic group (n=28). As disease control and healthy control group, 23 patients with vasculitis (16 female, 7 male; mean age 49±16 yrs), 8 patients with thrombosis (3 female, 5 male; mean age:55±11 yrs) and 25 healthy individuals (11 female, 14 male; mean age:37±10 yrs) were included to study. By using the modified rotation thromboelastogram, clotting time (CT), clot formation time (CFT) and maximum clot formation (MCF) were determined by INTEM and EXTEM analysis. Thrombocyte-leucocyte complexes and thrombocyte activation marker (p62) were investigated by flow-cytometric method. Results: In terms of thrombocyte-leucocyte complexes and P62 levels, no significant difference was found in female BD patients vs male BD pts, active BD pts vs inactive BD pts and thrombotic BD pts vs non-thrombotic BD pts. Thrombocyte-leucocyte complexes levels were higher in vasculitis group than BD group (p<0.01) and HC group (p<0.04). I-MCF was significantly prolonged in male BD patients than female BD patients. E-CFT was found to be shorter in male BD patients compared to female BD patients. E-MCF was statistically prolonged in male BD patients. In inactive male BD patients, while I-CFT was shorter than HC individuals, I-MCF and E-MCF were statistically prolonged than HC (p<0.02, p<0.03), respectively. However, No significant differences were found between inactive female BD patients and HC in terms of all ROTEM parameters. In active BD patients, E-CFT was shorter (p<0.02) and E-MCF was significantly prolonged than those of inactive BD patients (p<0.005). Conclusions: These results support that male BD patients have a hypercoagulable state compared to female BD patients which may be an explanation why male patients are prone to thrombotic complications. Disclosure of Interest: None declared